2019
DOI: 10.1177/0031512519888072
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcranial Direct Current Stimulation and Selective Motor Training Enhances Balance in Children With Autism Spectrum Disorder

Abstract: Previous studies have shown that transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) can facilitate the consolidation of motor skills in people who are typically developed, especially when tDCS is combined with goal-oriented exercises. Yet, the effect of tDCS on the motor skills of children with autism spectrum disorder is unknown. This study sought to investigate the effects of combined anodal tDCS and selective motor training on balance among 18 children with autism spectrum dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Among the many studies of intervention programs/training protocols aimed at improving balance in individuals with ASD, there have been interventions that can be classified as exercise- or sport-based, such as taekwondo, skating, karate, and aquatic exercise (Ansari et al, 2020; Casey et al, 2015; Cheldavi et al, 2014; Kim et al, 2016), videogame-based interventions (Fang et al, 2018; Travers et al, 2018), and sensory-based methods (Case–Smith et al, 2014; Pfeiffer et al, 2011). Some interventions have used new neuroscience technology such as transcranial direct current stimulation to improve balance in children with ASD (Mahmoodifar & Sotoodeh, 2019). Despite this variety among ASD interventions targeting balance, exercise-based interventions have been most common, and previous studies have shown their positive effects on the motor skills of children with ASD, including bilateral coordination, running speed, agility, and balance (Yin & Yin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among the many studies of intervention programs/training protocols aimed at improving balance in individuals with ASD, there have been interventions that can be classified as exercise- or sport-based, such as taekwondo, skating, karate, and aquatic exercise (Ansari et al, 2020; Casey et al, 2015; Cheldavi et al, 2014; Kim et al, 2016), videogame-based interventions (Fang et al, 2018; Travers et al, 2018), and sensory-based methods (Case–Smith et al, 2014; Pfeiffer et al, 2011). Some interventions have used new neuroscience technology such as transcranial direct current stimulation to improve balance in children with ASD (Mahmoodifar & Sotoodeh, 2019). Despite this variety among ASD interventions targeting balance, exercise-based interventions have been most common, and previous studies have shown their positive effects on the motor skills of children with ASD, including bilateral coordination, running speed, agility, and balance (Yin & Yin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cathodal stimulation over the left dlPFC is also applied in ASD (GÃmez et al., 2017 ) and in two open‐label studies that were not included in this review. Two recent studies also reported improving effects of frontocerebellar tDCS (i.e., anodal left dlPFC, cathodal right cerebellar tDCS) on behavioral symptoms (Toscano et al., 2019 ), and anodal stimulation over the primary motor cortex on motor skill training in children with ASD (Mahmoodifar & Sotoodeh, 2020 ). Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC, but not r‐TPJ tDCS, significantly improved ToM in children with ASD (Salehinejad et al., 2021 ).…”
Section: Resultsmentioning
confidence: 95%
“…and here, anodal tDCS over the left dlPFC (in 7 out of 11 studies) (Amatachaya et al, 2014;Amatachaya et al, 2015;Han et al, 2022;Kang et al, 2018;Qiu et al, 2021;Sun et al, 2022;Toscano et al, 2019) was the most often applied protocol in ASD. In one study (Hadoush et al, 2020) on behavioral symptoms (Toscano et al, 2019), and anodal stimulation over the primary motor cortex on motor skill training in children with ASD (Mahmoodifar & Sotoodeh, 2020). Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC, but not r-TPJ tDCS, significantly improved ToM in children with ASD .…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Cathodal stimulation over the left dlPFC is also applied in ASD 52 and in two open-label studies that were not included in this review. Two recent studies also reported improving effects of frontocerebellar tDCS (i.e., anodal left dlPFC, cathodal right cerebellar tDCS) on behavioral symptoms 55 , and anodal stimulation over the primary motor cortex on motor skill training in children with ASD 75 . Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC but not r-TPJ tDCS significantly improved ToM in children with ASD 76 .…”
Section: Autism Spectrum Disordermentioning
confidence: 91%
“…Of 11 included studies, only 1 study targeted right TPJ and vmPFC, two key regions in the theory of mind in ASD, and found that anodal vmPFC but not r-TPJ tDCS significantly improved ToM in children with ASD 76 . 9 of 11 studies had repeated protocols in which tDCS was applied on consecutive days for 10, 12, 15, or 20 sessions [52][53][54][55]70,71,[73][74][75] . All of these studies reported significant improvement of their outcome variables (mostly ASD symptoms) and repeated daily sessions…”
Section: Autism Spectrum Disordermentioning
confidence: 99%